2011
DOI: 10.1080/02791072.2011.605671
|View full text |Cite
|
Sign up to set email alerts
|

The Role of MDMA (Ecstasy) in Coping with Negative Life Situations Among Urban Young Adults

Abstract: This article examines the role of Ecstasy (MDMA or 3, 4-methylenedioxymethamphetamine) as a drug used for self-medication and coping with both short- and long-term negative life situations. We show that urban youth who do not have a specific diagnosed mental illness are more likely than those who have been diagnosed and have received treatment to use Ecstasy to cope with both situational stress and lifetime trauma. Diagnosed and treated youth sometimes self-medicate with other drugs, but do not choose Ecstasy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 68 publications
(80 reference statements)
1
14
0
Order By: Relevance
“…For MDMA, these findings were in line with previous observations showing an increased prevalence of psychiatric comorbidities in MDMA users (Keyes, Martins and Hasin 2008). However, because MDMA generally has mood elevating properties (Patel and Titheradge 2015; Wardle and de Wit 2014) and it has been shown that its use is the result of psychic suffering rather than its cause (Lieb et al 2002), the association between MDMA use and poor MH might best be explained by the users' attempts to selfmedicate (Moonzwe, Schensul and Kostick 2011;Scott et al 2013). However, as Parrot (2014) posited, using MDMA outside a supportive, therapeutic context -as typically done in self-medication -can bring out negative feelings while the user is under the effects of the drug.…”
Section: Discussionsupporting
confidence: 88%
“…For MDMA, these findings were in line with previous observations showing an increased prevalence of psychiatric comorbidities in MDMA users (Keyes, Martins and Hasin 2008). However, because MDMA generally has mood elevating properties (Patel and Titheradge 2015; Wardle and de Wit 2014) and it has been shown that its use is the result of psychic suffering rather than its cause (Lieb et al 2002), the association between MDMA use and poor MH might best be explained by the users' attempts to selfmedicate (Moonzwe, Schensul and Kostick 2011;Scott et al 2013). However, as Parrot (2014) posited, using MDMA outside a supportive, therapeutic context -as typically done in self-medication -can bring out negative feelings while the user is under the effects of the drug.…”
Section: Discussionsupporting
confidence: 88%
“…MMP reported a greater likelihood of lifetime use of hallucinogens and greater lifetime use/misuse of most other drugs than NPU. Overall, the pattern of greater history of substance use among MMP may be attributed to a general pattern of self-medication (McCabe et al, 2009; Moonzwe et al, 2011) or sensation-seeking (McCabe et al, 2015) among some young adults, who were then inclined to seek a recommendation for medical marijuana. However, 90-day substance use comparisons between MMP and NPU were different than lifetime comparisons.…”
Section: Discussionmentioning
confidence: 99%
“…For others, participating in the rave experience may be spiritual experience (St. John, 2004); however, other reasons for drug use among party attendees may be to self-medicate or “fit in” with particular social groups (Hunt et al, 2009a; Kubicek et al, 2007; Mansergh et al, 2001; Moonzwe et al, 2011). …”
Section: Introductionmentioning
confidence: 99%